Os ovos da serpente : a potência totalitária das ideias autoritárias nas democracias contemporâneas - Rigon, Bruno Silveira (2015)
This work aims to identify which are the continuities of ideas that affected and legitimized the Nazism totalitarianism and the Latin American national security dictatorships presents in contemporary ideas, mainly in criminological, criminal political and criminal juridical thought. For that, the analyses will start of epistemological bases of history of ideas and the notion of state of exception. First of all, we approach the genealogy of national-socialist ideology. After, we analyze the genealogy of national security ideology. In the final chapter, we have confirmed the hypothesis that exists continuities between the authoritarian ideas of the past and democratic ideas in the present and we tried to identify in which contemporary ideas and in which degree occurs this approximation. Considering that authoritarian ideas are metamorphosed, we aim to realize yours transformations in contemporary thought.